Fabrication and in vitro biocompatibilities of fibrous biocomposites consisting of PCL and M13 bacteriophage-conjugated alginate for bone tissue engineering. Issue 4 (23rd December 2015) - Lee, Jae Yoon; Chung, Jinhyo; Chung, Woo-Jae; Kim, GeunHyung
Abstract : We propose a new biocomposite consisting of M13-phage-conjugated alginate and PCL micro/nanofibers, and it has potential to be used as an excellent bioactive component for hard tissue regeneration. Abstract : As the M13 bacteriophage, which has integrin binding and calcium binding sites, provides topological cues from the nanofibrous shape and biochemical cues from the Arg–Gly–Asp (RGD) sequence attached to the surface of fibrous phage, it has been recommended as a bioactive component for use in bone tissue engineering. However, although it has good biological activities, its low mechanical properties and low processing ability represent major issues that must be overcome before its use as a tissue engineering substitute. To overcome these issues, we chemically conjugated the M13 bacteriophage and alginate with a cross-linking agent and it was used as a bioactive component on electrospun poly(ε-caprolactone) (PCL) micro/nanofibres. Assessment of the physical properties and in vitro biocompatibility using osteoblast-like cells indicated that the biocomposite supplemented with the conjugated phage/alginate was mechanically enhanced, and the extent of mineralisation of cells on the composite was significantly higher compared to that on the fibrous composites fabricated using physically mixed M13 phage/alginate and RGD-modified alginate. These results indicate that M13 phage-conjugated alginate may have potential to be used as an excellent bioactive component for bone tissue regeneration.